Adjustment Delay Scheme to Improve Performance IEEE 802.15.4 Networks - Eppy Yundra; Bih-Hwang Lee (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The challenges of CSMA/CA as following: first, when the device nodes detect the channel in busy condition, the device nodes have to increase the value of backoff exponent which cause range of blind backoff process also increase. Second, the blind backoff process will cause lower channel utilization and more energy consumptions. This article proposes a scheme to improve IEEE 802.15.4 medium access control, called adjustment delay scheme (ADES). This article also presents a comprehensive Markov chain analysis to predict the probability of successful transmission, network goodput, bandwidth utilization and total network energy consumption. The validity of the model analysis is proven by precisely matching the simulation experiments. ADES performs better than those of other algorithms in term of the probability of successful packet transmission, network goodput, bandwidth utilization as well as energy consumption in the networks.